2018
DOI: 10.1186/s13071-018-2777-9
|View full text |Cite
|
Sign up to set email alerts
|

Wolbachia diversity and cytoplasmic incompatibility patterns in Culex pipiens populations in Turkey

Abstract: BackgroundWolbachia are maternally transmitted bacteria that can manipulate their hosts’ reproduction causing cytoplasmic incompatibility (CI). CI is a sperm-egg incompatibility resulting in embryonic death. Due to this sterilising effect on mosquitoes, Wolbachia are considered for vector control strategies. Important vectors for arboviruses, filarial nematodes and avian malaria, mosquitoes of Culex pipiens complex are suitable for Wolbachia-based vector control. They are infected with Wolbachia wPip strains b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
(85 reference statements)
0
34
0
Order By: Relevance
“…A total of 67 isofemale lines were established from larvae collected at four sites in the province of Trento in the North‐East of Italy (San Michele all'Adige, Roveré Della Luna, Mezzocorona and Zambana: Data ), because it was already known that w Pip strains from the w PipIV group occurred in this area (Dumas et al, ). The PCR‐RFLP test as described in Altinli et al () confirmed that all isofemale lines were infected with w PipIV strains. Crosses between males from these 67 isofemale lines and females from the w PipI Tunis laboratory line (reference line used for the screening) led to sort the lines according to the two mod phenotypes previously described (Atyame et al, ; Bonneau, Atyame, et al, ): the males from 62 isofemale lines from North Italy were found incompatible with Tunis females (qualified as incompatible isofemale lines) and five lines exhibited males compatible with Tunis females (qualified as compatible isofemale lines: Data ).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…A total of 67 isofemale lines were established from larvae collected at four sites in the province of Trento in the North‐East of Italy (San Michele all'Adige, Roveré Della Luna, Mezzocorona and Zambana: Data ), because it was already known that w Pip strains from the w PipIV group occurred in this area (Dumas et al, ). The PCR‐RFLP test as described in Altinli et al () confirmed that all isofemale lines were infected with w PipIV strains. Crosses between males from these 67 isofemale lines and females from the w PipI Tunis laboratory line (reference line used for the screening) led to sort the lines according to the two mod phenotypes previously described (Atyame et al, ; Bonneau, Atyame, et al, ): the males from 62 isofemale lines from North Italy were found incompatible with Tunis females (qualified as incompatible isofemale lines) and five lines exhibited males compatible with Tunis females (qualified as compatible isofemale lines: Data ).…”
Section: Resultsmentioning
confidence: 78%
“…The PCR-RFLP test as described in Altinli et al (2018) confirmed that all isofemale lines were infected with wPipIV strains. Crosses between males from these 67 isofemale lines and females from the wPipI Tunis laboratory line (reference line used for the screening) led to sort the lines according to the two mod phenotypes previously described (Atyame et al, 2015;Bonneau, Atyame, et al, 2018): the males from 62 isofemale lines from North Italy were found incompatible with Tunis females (qualified as incompatible isofemale lines) and five lines exhibited males compatible with Tunis females (qualified as compatible isofemale lines: Data S1).…”
Section: Both Compatible and Incompatible Mod Phenotypes Are Presenmentioning
confidence: 75%
“…To test the effect of the Wolbachia genetic differences on CpDV amount and their vertical transmission we used three isofemale lines Tunis, Harash and Slab (Supporting Information Table 1) that are infected with wPip I, wPip IV and wPip III respectively. wPip groups of these lines have been assigned based on a PCR/RFLP test on pool of larvae using pk1 primers as previously described (Dumas et al, 2013;Altinli et al, 2018) and were regularly verified during the experiments. We introduced the cytoplasm of Tunis and Harash lines, along with their respective wPip strains, into the Slab nuclear background as described by Duron and colleagues (2012).…”
Section: Backcrossesmentioning
confidence: 99%
“…mosquitoes but was not found in A. aegypti. Further characterization of the presence and strain types of locally occurring insect-specific viruses and Wolbachia is important (77,78) for possible biologically based control interventions (66,79,80). This study presents the broad detection capability, sensitivity, and ease of use of the LLMDA approach for surveillance of mosquito-borne diseases of medical importance.…”
Section: Discussionmentioning
confidence: 99%